Micro‐Practices of Strategic Sensemaking and Sensegiving: How Middle Managers Interpret and Sell Change Every Day* - Rouleau, Linda (Journal of Management Studies, 2005)
abstract This paper looks at the workings of ongoing primary sensemaking and sensegiving micro‐practices by which middle managers interpret and sell strategic change at the organizational interface. Through middle managers’ routines and conversations related to the implementation of a strategic change in a top‐of‐the‐line clothing company, the article shows how they contribute to renewing links with stakeholders, in particular clientele, by drawing on their tacit knowledge. Interpretative analysis of these routines and conversations highlights four micro‐practices of strategic sensemaking and sensegiving: translating the orientation, overcoding the strategy, disciplining the client, and justifying the change. The paper outlines a practice perspective of sensemaking and sensegiving. It ends by suggesting the necessity of looking at middle managers’ role as interpreters and sellers of strategic change at the micro level for a better understanding of their contribution in sustaining competitive advantage through their everyday activities.